Instructor Interaction and Immediacy Behaviors in a Multipoint Distance Educational Environment: Using Technology to Improve Low-Incidence Teacher Preparation. Issue 4 (December 2013) - Bohnstedt, Kathy D.; Jerome, Marci Kinas; Lojkovic, David A.; Brigham, Frederick J.; Behrmann, Michael M.
The purpose of this study was to examine the experiences of professors teaching in a multipoint videoconferencing instructional environment and how they interacted with students in proximate and remote classrooms. Qualitative and quantitative data were analyzed to gain an understanding of the teaching experience and to examine differences between instructor interaction and immediacy behaviors based on student location. Results indicated that no clear difference existed in instructor interaction behaviors with local and remote populations, but that they engaged in more immediacy behaviors with the remote population.